Oral Potentially Malignant Disorders: A review on Bangladesh perspective (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Oral potentially malignant disorders (OPMDs) are a group of chronic conditions affecting the oral mucosa with a risk of transformation to oral squamous cell carcinoma (OSCC). Oral leukoplakia, oral submucous fibrosis, oral lichen planus, and oral erythroplakia are the most common OPMDs observed in South Asian population. However, oral leukoplakia and oral lichen planus are commonly encountered OPMDs in clinical practice in Bangladesh, possibly, owing to specific lifestyle habits. Although the exact aetiology is unknown, use of smokeless tobacco, smoking, and chewing of betel quid containing areca nut, are considered as common risk factors for OPMDs. Early diagnosis is very important and can be lifesaving, as at a late stage, OPMDs are more likely to progress into severe dysplasia or even into squamous cell carcinoma. In fact, OPMDs have a significantly increased risk of progressing to cancer, mostly in South Asian population, including Bangladesh. This review provides an overview of the OPMDs in Bangladeshi population.  J Bangladesh Coll Phys Surg 2023; 41(4): 305-314